2019
DOI: 10.1017/s1460396919000633
|View full text |Cite
|
Sign up to set email alerts
|

A review of ultrasound-mediated microbubbles technology for cancer therapy: a vehicle for chemotherapeutic drug delivery

Abstract: Background:The unique behaviour of microbubbles under ultrasound acoustic pressure makes them useful agents for drug and gene delivery. Several studies have demonstrated the potential application of microbubbles as a non-invasive, safe and effective technique for targeted delivery of drugs and genes. The drugs can be incorporated into the microbubbles in several different approaches and then carried to the site of interest where it can be released by destruction of the microbubbles using ultrasound to achieve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Due to the physical characteristics of US and the cost effective, safe and non-invasive manner of its use [ 12 ], US is widely applied for either diagnostic imaging or therapeutic purposes (e.g., tumor tissue ablation [ 14 ], physiotherapy [ 15 ], kidney stone comminution [ 16 ]), or the combination of both (“Theranostics”)) [ 17 ].…”
Section: Physics Of Ultrasound and Its Biological Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the physical characteristics of US and the cost effective, safe and non-invasive manner of its use [ 12 ], US is widely applied for either diagnostic imaging or therapeutic purposes (e.g., tumor tissue ablation [ 14 ], physiotherapy [ 15 ], kidney stone comminution [ 16 ]), or the combination of both (“Theranostics”)) [ 17 ].…”
Section: Physics Of Ultrasound and Its Biological Effectsmentioning
confidence: 99%
“…In controlled release systems (smart drug delivery systems, SDDS), stimuli-responsive nanocarriers (e.g., responsive to ultrasound) are used that are able to release their payload on demand at the tumor tissue site, preventing premature drug loss. Ultrasound (US), which has been extensively applied in clinics for both diagnostic purposes and treatment, is considered as one of the promising triggers for stimuli-responsive drug delivery nanosystems due to its capability to non-invasively penetrate deeply into the tissue without damaging it [12]. Beyond efficacy considerations, toxicological aspects (biocompatibility) and safety issues play an important role in this context as well and are major barriers for the translation of this promising technology towards clinical application [13].…”
Section: Introductionmentioning
confidence: 99%
“…They also confirmed that the shell properties of MBs are also strongly affected by the US intensity (Leong‐Poi et al, ). Indeed, the behavior of MBs in an acoustic filed is significantly influenced by the viscoelastic properties of the shell that are ultimately dependent on the composition and thickness of the shell (de Jong, Hoff, Skotland, & Bom, ; Osei & Al‐Asady, ).…”
Section: Development Of Ultrasound‐responsive Microbubbles: Physiochementioning
confidence: 99%
“…Various nano- and microsystems, including micelles, liposomes, and microbubbles, have been developed as imaging agents and to selectively deliver chemotherapeutics to tumor cells [ 1 6 ]. An increased specificity for tumor cells can be gained through ligand-mediated active targeting, which involves the use of targeting ligands, such as monoclonal antibodies, antibody fragments, proteins, peptides, and other small molecules, including vitamins and carbohydrates [ 7 8 ].…”
Section: Introductionmentioning
confidence: 99%